"Little girl, where do you think you go with this method?": shame and use of emergency contraception. (30th September 2020) - Cantarero Arevalo, L; Merchant, E
Abstract: Background: In England in 2018, 45% of pregnancies were unplanned at the time of conception. In 2017, there were 192, 900 abortions carried out for women residing in England and Wales, with the highest rate of abortion being for women aged 20-24 (28.2 per 1000 resident women). Aim: To understand social and cultural influences which affect ethnic minority young women's utilization and experience of emergency contraception in the United Kingdom. Methods: Qualitative in-depth interviews following an interview topic guide were conducted with seven young women currently living in the UK, whose parents were born outside the UK. Interviews were recorded, transcribed and input into NVivo version 11.4.3. Transcriptions were coded to identify themes and these themes were then analyzed to identify commonalities and establish connections to understand perceptions and experiences of the participants. The themes coded were "Knowledge of emergency contraception", "relationships" "concerns about obtaining and using EC", "balancing risks" and "religion and culture". Results: Participants were often not open with their parents about sexual health related topics. Cultural taboos still persist towards sex before marriage which could translate into guilt and shame about using EC. When asked about concerns surrounding EC, participants mentioned concerns relating to obtaining EC, generally involving privacy embarrassment or shame. Stigma and concern about what others may think was a fairly frequent theme throughout the interviews, with participants being worried about what friends, family or service providers would think about them. Conclusions: cultural awareness in healthcare reiterate the need for interventions which take into consideration sociocultural contexts. This is essential to ensure that young women have access to emergency contraception in order to prevent unwanted pregnancy. Key messages: Despite availability of emergency contraception, young women still face the risk of going through an unwanted pregnancy becuase of embarrasment and shame. Cultural taboos towards sex before marriage still persists and this is translated into guilt and shame about using emergency contraception.